Psychological growth and well-being in individuals born with cleft: An application of self-determination theory. Issue 4 (3rd April 2017) - Searle, Aidan; Neville, Patricia; Waylen, Andrea
Abstract : Objective: Many studies of individuals born with cleft lip and/or palate (CLP) address the psychological impact of CLP in terms of stigma and/or 'resilience'. The present study challenges the usefulness of resilience in CLP research with the application of self-determination theory (SDT). It is proposed that SDT can serve to better understand how individuals born with CLP can achieve psychological growth and well-being. Design: Interviews were conducted with 15 individuals born with CLP in the UK. Results: A thematic analysis was conducted and four main themes emerged: (1) personal challenges, (2) support and strategies for social interaction, (3) experience of treatment and outcomes, and (4) personal development. The thematic analysis and the interpretation in the context of SDT leads to a greater understanding of the development of psychological growth and well-being in individuals born with CLP. Conclusion: Interpreting the life experiences of individuals with CLP through the theoretical lens of SDT allows the conceptualisation of individuals with CLP as a positive psychological resource when faced with the exclusionary practice of stigma. This resourcefulness is primarily nurtured by a supportive family and social environment that leads to the development of positive psychological growth and well-being. A new direction in CLP research is proposed that seeks to inform and implement change in professional practice to support individuals with CLP and their families.